Animal physiotherapy : (Blackwell Pub., 2007)
The book provides an essential reference guide for physiotherapists looking to apply the proven benefits of physiotherapy to the treatment of companion and performance animals. It reviews the scientific principles behind the practice of physiotherapy, and what it can achieve and essential applied background information on animal behaviour, nutrition, biomechanics and exercise physiology